2018
DOI: 10.1038/gim.2018.39
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing reanalysis at 12 months boosts diagnosis and is cost-effective when applied early in Mendelian disorders

Abstract: PurposeWhole-exome sequencing (WES) has revolutionized Mendelian diagnostics, however, there is no consensus on the timing of data review in undiagnosed individuals and only preliminary data on the cost-effectiveness of this technology. We aimed to assess the utility of WES data reanalysis for diagnosis in Mendelian disorders and to analyze the cost-effectiveness of this technology compared with a traditional diagnostic pathway.MethodsWES was applied to a cohort of 54 patients from 37 families with a variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
156
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(164 citation statements)
references
References 38 publications
6
156
1
1
Order By: Relevance
“…Of note, 11 cases classified as nondiagnostic in this study were ultimately clinically diagnosed with multiple system atrophy, cerebellar type, and another case was identified with a VUS associated with increased risk for this condition (Gilman et al, ; Zhao et al, ). We also reclassified variants from our previously reported 76 cases (Fogel et al, ) based on current annotation, which has been shown to improve diagnosis over time (Alfares et al, ; Ewans et al, ; Fogel, ; Fogel, Lee, Strom, Deignan, & Nelson, ; Fogel et al, ; Nambot et al, ; Rexach et al, ; Wright et al, ). This resulted in four cases previously classified as nondiagnostic or having a reportable VUS being reclassified with a pathogenic/likely pathogenic genetic variant.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, 11 cases classified as nondiagnostic in this study were ultimately clinically diagnosed with multiple system atrophy, cerebellar type, and another case was identified with a VUS associated with increased risk for this condition (Gilman et al, ; Zhao et al, ). We also reclassified variants from our previously reported 76 cases (Fogel et al, ) based on current annotation, which has been shown to improve diagnosis over time (Alfares et al, ; Ewans et al, ; Fogel, ; Fogel, Lee, Strom, Deignan, & Nelson, ; Fogel et al, ; Nambot et al, ; Rexach et al, ; Wright et al, ). This resulted in four cases previously classified as nondiagnostic or having a reportable VUS being reclassified with a pathogenic/likely pathogenic genetic variant.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that WES‐based techniques are new diagnostic strategies for early detection of Mendelian disorders (Ewans et al, ). Our cohort included 40 Chinese nonconsanguineous families with recurrent fetal malformations during the prenatal ultrasound screening.…”
Section: Discussionmentioning
confidence: 99%
“…The two pathogenic findings on CMA (del 1p36 and dup 15q11. [2][3][4][5][6][7][8][9][10][11][12][13] were present in patients with clinical phenotypes consistent with these copy number variants, and these were not detected by research WES analysis.…”
Section: Participants With Concomitant "Positive" Clinical Testingmentioning
confidence: 99%
“…The case above illustrates the importance of revisiting a patient's genetic data over time and illustrates the complex environment of clinical testing, in which not all modalities are available to patients in all settings due to variability in clinical provider awareness, institutional practices, and cost/insurance‐related barriers. With the evolution of genetic testing modalities, continued identification of epilepsy genes, and improved cataloging of knowledge about specific gene variants, a patient whose testing was "negative" years or months ago may have an identifiable genetic etiology upon reanalysis . Given that approximately 70%‐80% of patients with otherwise unexplained epilepsy are thought to have an underlying genetic cause, the genetic evaluation of patients with epilepsy is becoming more routine in clinical practice, particularly with the rationale that identifying genetic causes for epilepsy may guide treatment options for some patients and limit the need for ongoing additional testing.…”
Section: Introductionmentioning
confidence: 99%